2012
DOI: 10.1111/j.1745-9133.2012.00802.x
|View full text |Cite
|
Sign up to set email alerts
|

Overview of: “Getting the Law Involved a Quasi‐Experiment in Early Intervention Involving Collaboration Between Schools and the District Attorney's Office”

Abstract: Research Summary  Precursors to serious and chronic delinquency often emerge in childhood, stimulating calls for early interventions. Most intervention efforts rely solely on social service programs—often to the exclusion of the juvenile justice system. The juvenile justice system has been reluctant to become involved in the lives of relatively young children fearing net widening or further straining resources that could be used for older youth with documented delinquency histories. We report here the results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Early intervention is considered a promising avenue for addressing youth's behavioral problems (e.g., [25,80]), but the results from this study indicate that younger adolescents fare worse than their older counterparts in terms of negative consequences related to arrest, calling into question the types of early intervention that should be utilized. To be sure, this is not to say that early intervention is not warranted in some cases, but it is necessary to understand the potential consequences that all types of intervention have and most notably, interventions that rely on official actors of the justice system.…”
Section: Discussionmentioning
confidence: 86%
“…Early intervention is considered a promising avenue for addressing youth's behavioral problems (e.g., [25,80]), but the results from this study indicate that younger adolescents fare worse than their older counterparts in terms of negative consequences related to arrest, calling into question the types of early intervention that should be utilized. To be sure, this is not to say that early intervention is not warranted in some cases, but it is necessary to understand the potential consequences that all types of intervention have and most notably, interventions that rely on official actors of the justice system.…”
Section: Discussionmentioning
confidence: 86%
“…Nonetheless, recent research on school resource officers has produced mixed findings regarding their theorized contribution to the school-to-prison pipeline, suggesting that the community or school may have a moderating effect (Fisher & Hennessy, 2016; May, Barranco, Stokes, Robertson, & Haynes, 2015; Nance, 2016). Limited evidence from early intervention programs successful at significantly reducing school suspensions and improving associated outcomes have shown that the authority of the court may serve to compel some uncooperative parents of delinquent youth to, “utilize available services in order to address their child’s problems” (Wright, McMahon, Daly, & Haney, 2012, p. 245). Additionally, findings concerning other prosecutorial and family-based interventions targeting at-risk children suggest that these strategies are effective but may require intensive case management with intellectually deficient subjects and often necessitate community-wide mobilization (Farrington, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Many types of prevention programs, especially those that focus on adolescents, involve justice personnel such as police, prosecutors, or probation officers. In these cases, justice personnel work in close collaboration with those from such areas as education, health care, recreation, and social services (see, for example, Wright et al, 2012). 2.…”
Section: Acknowledgementsmentioning
confidence: 99%